Robust onionlike structures with magnetic and photodynamic properties formed by a fullerene C60–POM hybrid. Issue 82 (21st September 2016) - Zhou, Shengju; Feng, Yongqiang; Chen, Mengjun; Li, Qian; Liu, Baoyong; Cao, Jiamei; Sun, Xiaofeng; Li, Hongguang; Hao, Jingcheng
Abstract : A fullerene C60 –Dawson POM hybrid was prepared for the first time, which can aggregate into onionlike structures with magnetic and photodynamic properties. Abstract : We report for the first time the synthesis of a covalently-linked fullerene C60 –Dawson POM hybrid, which can form onionlike structures with rich magnetic, electrochemical and photodynamic properties.